The Influence of Peer Assessment and the Use of Corpus for the Development of Speaking Skills in In-Service Teachers - Mary Mily Gómez Sará (Asociación Colombiana de Profesores de Ingles, 2016)
This article reports on how the use of peer-assessment and a corpus influence the development of the spontaneous interactive speaking of 14 adults with an A1 English level. The data, that were collected through video recordings, two peer-assessment forms, and a teacher's journal, evidenced the development of three enhancement strategies (willingness to improve, use of compensatory strategies, and construction of a personalized version of the corpus) and two detrimental traits (underassessment and dependency on the corpus).The results of the inquiry evinced some limitations in the pedagogical intervention.